2014
DOI: 10.1111/1440-1681.12235
|View full text |Cite
|
Sign up to set email alerts
|

Association of nitric oxide synthase 3 (NOS3) 894 G>T polymorphism with prognostic outcomes of anthracycline in Chinese patients with acute myeloid leukaemia

Abstract: The aim of the present study was to investigate the influence of the nitric oxide synthase 3 (NOS3) 894 G>T polymorphism on prognostic outcomes of anthracycline in Chinese patients with de novo intermediate-risk acute myeloid leukaemia (AML) and to examine the gene expression level in relation to genetic variation. In all, 225 Chinese patients with intermediate-risk AML (at the complete remission stage) treated with anthracycline were enrolled in the study. The 894 G>T polymorphism of the NOS3 gene was analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
1
3
1
Order By: Relevance
“…VEGFR-2 (KDR) is a key signal sensor for physiological and pathological angiogenesis, and a previous study showed that VEGFR-2 can directly or indirectly promote the proliferation of HL-60 cells, revealing that VEGFR-2 can be a target for drug intervention, inhibit tumor cell proliferation and promote apoptosis [ 36 ]. Endothelial nitric oxide synthase 3 (NOS3) is involved in regulating the production of ROS, which plays an important antitumor role in AML patients and can stimulate leukemia-related apoptotic pathways through oxidative stress, DNA damage, membrane damage, and lipid peroxidation; NOS3 is correlated with the overall survival of AML patients [ 37 ], and this finding is consistent with our survival analysis. VAV family genes (VAVs), which are located downstream of protein tyrosine kinases, including VAV1, VAV2, and VAV3, are signal transduction molecules that are regulated by tyrosine phosphorylation and are associated with the occurrence, progression, and prognosis of many cancers [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…VEGFR-2 (KDR) is a key signal sensor for physiological and pathological angiogenesis, and a previous study showed that VEGFR-2 can directly or indirectly promote the proliferation of HL-60 cells, revealing that VEGFR-2 can be a target for drug intervention, inhibit tumor cell proliferation and promote apoptosis [ 36 ]. Endothelial nitric oxide synthase 3 (NOS3) is involved in regulating the production of ROS, which plays an important antitumor role in AML patients and can stimulate leukemia-related apoptotic pathways through oxidative stress, DNA damage, membrane damage, and lipid peroxidation; NOS3 is correlated with the overall survival of AML patients [ 37 ], and this finding is consistent with our survival analysis. VAV family genes (VAVs), which are located downstream of protein tyrosine kinases, including VAV1, VAV2, and VAV3, are signal transduction molecules that are regulated by tyrosine phosphorylation and are associated with the occurrence, progression, and prognosis of many cancers [ 38 ].…”
Section: Discussionsupporting
confidence: 87%
“…The SNPs rs1799983 and rs2070744 of NOS3 have been associated with lower levels of the enzyme [13,27], as well as with lower survival [27]. In our cohort, opposing associations were observed in toxicity between both polymorphisms, not previously described.…”
Section: Discussioncontrasting
confidence: 45%
“…The variant allele of NOS3 rs1799983 was associated with a protective effect against nephrotoxicity and thrombocytopenia, which had already been associated with a protective effect against cardiotoxicity [28]. In contrast, the minor allele of NOS3 rs2070744 increased hepatotoxicity and thrombocytopenia, probably related to lower activity of the enzyme [13,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that NOS3 Glu298Asp polymorphism in homozygosis increased the risk of thrombosis in a cohort of patients with essential thrombocythemia or prefibrotic PMF. 56, 57 …”
Section: Resultsmentioning
confidence: 99%